Teachers’ Lived Experiences in Early Childhood Sexual Literacy: A Phenomenological Inquiry in the Indonesian Context - Hadiqotul Luluk; Barokah Widuroyekti; Sri Tatminingsih; Mukti Amini; Esti Kurniawati Mahardika (Universitas Pendidikan Ganesha, 2025)
Sexual violence in early childhood was a disturbing phenomenon that needed to be addressed. Although quite a few studies had examined this issue, not many had employed the teacher’s perspective phenomenologically. Therefore, this study aimed to analyze the obstacles and solutions proposed by teachers in teaching the concept of sexual literacy to young children. The research design used was phenomenology. A total of 18 teachers (with 8 months to 30 years of teaching experience, all women aged 20–51 years) participated in the study. The teachers’ sexual literacy perception questionnaire was used as the instrument. Data were analyzed using thematic analysis. The findings revealed that topics such as gender identity and the boundaries of body parts that could and could not be touched by others were considered essential to be taught. The main obstacles encountered included the lack of visual aids appropriate for children’s developmental levels and the perception among some parents that discussing sexual literacy with young children was taboo. In conclusion, there was a limitation in the availability of visual aids for teaching sexual literacy in schools. Therefore, the implication was that early childhood education teachers should prepare instructional tools, such as sex education games, to help prevent sexual harassment against children.